Smoldering Ignition and Transition to Flaming Combustion of Pine Needle Fuel Beds: Effects of Bulk Density and Heat Supply - Jiuling Yang; Jiepei Xu; Xiang Wu; Haoliang Wang (Fire)
The smoldering of pine needle fuel beds (PNBs) has been a common subject of research because of its importance in initiating the rekindling of forest floor fires. Experimental studies of the coupling effects of the bulk density and external heat supply on smoldering in PNBs have been scarce up to now. In this study, laboratory smoldering experiments were conducted to study the coupling effects of bulk density (30–55 kg m−3) and heat supply (ignition-off temperature Toff = 190 °C and 230 °C). Different ignition modes were observed under the same conditions, including non- ignition (NI), flaming ignition (FI), and the smoldering-to-flaming (StF) transition. The results in this study showed that the bulk density had distinct effects on different ignition modes: the increase in the bulk density facilitated the StF transition but impeded the FI. The coupling effects between the bulk density and heat supply became more intricate, especially at lower bulk densities and at a reduced heat supply. Additionally, a simple energy balance equation was established to explain the coupling effects of bulk density and heat supply on ignition behavior. The critical mass loss rate (MLR) for the StF transition ranged from 0.01 g s−1 to 0.03 g s−1, while the critical MLR for FI was 0.035 g s−1. The modified combustion efficiency (MCE) index for the StF transition decreased from approximately 79.6% to 70.1% as the density increased from 30 kg m−3 to 55 kg m−3. In contrast, the MCE for FI was approximately 90% across all the bulk densities. The StF transition delay time increased from 50 s at 30 kg m−3 to 1296 s at 55 kg m−3 when Toff = 230 °C. Further reduction in heat supply led to an increase in the delay time for the StF transition by diminishing the intensity of smoldering combustion. This work advances the fundamental understanding of how heat supply and bulk density impact smoldering ignition modes, ultimately aiding in the development of wildfire prevention strategies.